Recortes do psicodrama e do pensamento complexo contribuindo para o desenvolvimento da relação professor-aluno - Pontes, Rosa Lidia Pacheco Ferreira (2006)
The problem that guided this work was the inquiring about the possibility of making approaches and, or, finding theoretic complementarities between Jacob Levy Moreno and Edgar Morin, referring to the human being and his relationships, and more specifically referring to the education one, with the final objective of elaborating an educative project integrating theoretic and methodologically the two authors, aiming to sensitize professors to their relation practices with students. The theoretic research began with an investigation of the following clips: Human knowledge, God: human being and world s origin, Man as a cosmic being, Human relations: possibilities and difficulties, Man internal s world and his relations, and, Creativity in human relations. Once found the approaches and complementarities in relationship in the selected clips, the second step was creating three educative categories to be studied: Relationship knowledge blindness, Relationship incertitude, and Comprehension teaching. Verified the possibilities of approaching and complimentarily also in these categories, the first inquiring of the research was confirmed. Then, an educative project was elaborated integrating the ideas of the two authors using Sociodrama as method, with the objective of sensitizing professors to their relation practices with students.